Deployment of Caller Location Services within Sierra Leone's 117 Ebola Response Centre. (2015) - Eyres, Peter John; Brown, Leo; Rohan, Hana
Abstract: The effectiveness of both emergency services and response planning functions in humanitarian response and public health crises are significantly enhanced by the availability of location services in mobile networks. Here we describe how eHealth Africa and Netfuse Telecom are working together to use mobile network location services to improve the operational effectiveness of the 117 Ebola response call centre and support decision making and resource allocation at the National Ebola Response Centre, which is coordinating the response to the Ebola epidemic in Sierra Leone.